Bach perspectives. - Talle, Andrew (Bach perspectives., 2013)
In this volume, Wolfgang Hirschmann proposes an ethnographic approach that contextualizes Bach's works, addressing the aesthetic paths he took as well as those he did not pursue. Steven Zohn's essay considers Telemann's contribution to the orchestral Ouverture genre, observering how Telemann's approach to integrating the national styles of his time was quite different from, but no less rich than, Bach's Andrew Talle compares settings and strategies of Vergnüte Ruh, beliebte Seelenlust by Bach and Graupner. Alison Dunlop presents valuable primary research on Muffat, the most commonly cited keyboard music composer in Vienna during Bach's lifetime. Finally, Michael Maul sheds new light on the Scheibe-Birnbaum controversy, contextualizing the most famous critique of J.S. Bach's compositional style by discussing the other composers that Scheibe critiqued.